The Effect of Brand Image on Consumer Buying Interest (Case Study of Tenth Avenue Mall Bandung 2025) - Yulia Nurhayati; Riska Aprilina; Astri Wulandari (Danadyaksa: Post Modern Economy Journal, 2026)
The increasing competition among shopping malls in Bandung requires each mall to have a strong Brand Image in order to attract consumers’ purchase intention. Brand Image is an important factor as it influences consumers’ perceptions, attitudes, and interest in choosing a shopping destination. This final project aims to analyze the Brand Image, consumers’ purchase intention, and the effect of Brand Image on consumers’ purchase intention at Tenth Avenue Mall Bandung. The research method used in this final project is a quantitative method with descriptive and verificative research types. Data were collected through questionnaires distributed to consumers who have visited or are familiar with Tenth Avenue Mall Bandung. The data analysis techniques applied include descriptive analysis and simple linear regression analysis using statistical software. The results show that the Brand Image of Tenth Avenue Mall Bandung is categorized as good, while consumers’ purchase intention is at a moderate to high level. Furthermore, the verificative analysis indicates that Brand Image has a positive and significant effect on consumers’ purchase intention. The conclusion of this final project is that a better Brand Image leads to a higher level of consumers’ purchase intention. The results of this final project are expected to provide useful input for management in improving marketing strategies and to serve as a reference for future research.